ANALISIS KUALITAS SINYAL WIFI PADA UNIVERSITAS MUSLIM INDONESIA - Erick Irawadi Alwi (Faculty of Computer Science, University of Jember, 2019)
Indonesian Muslim universities utilize WiFi networks as a facility to support the implementation of student and academic lecture activities within the scope of Indonesian Muslim universities. However, with the number of Indonesian Muslim University students around 17,000 people, internet access to the internet network has become slow. In addition, there are several faculties on several floors that do not get wifi signals or get weak signals so students cannot enjoy the internet network. Because it is necessary to measure the signal quality on wireless devices (AP) in each faculty in the scope of UMI with action research methods and analyze the signal quality so that it is known what factors can cause the wifi signal to sometimes be weak or not even get a signal at all